Bureaucracy, influence and beliefs: A literature review of the factors shaping the role of a safety professional. (October 2017) - Provan, David J.; Dekker, Sidney W.A.; Rae, Andrew J.
Highlights: There are 25 institutional, relational and individual factors that shape the practice of safety professionals. Safety professionals relate to stakeholders within organizations through; challenge, authority, influence and alliance. Practical implications for safety professional practice are synthesized from reviewing 30 years of research. Abstract: Safety professionals have been working within organizations since the early 1900s. During the past 25 years, societal pressure and political intervention concerning the management of safety risks in organizations has driven dramatic change in safety professional practice. What are the factors that influence the role of safety professionals? This paper reviews more than 100 publications. Thematic analysis identified 25 factors in three categories: institutional, relational, and individual. The review highlights a dearth of empirical research into the practice and role of safety professionals, which may result in some ineffectiveness. Practical implications and an empirical research agenda regarding safety professional practice are proposed.